PERAN KEGIATAN MANASIK HAJI PADA PERKEMBANGAN AGAMA DAN MORAL ANAK USIA DINI DI RA ARAFAH SIPOLU-POLU - Annisa Wahyuni; Silva Hidayah Nst, Farah Fadhilah Nasution, Pitri Hamidah, Fuji Atika Rahmah (CV. ADIBA AISHA AMIRA, 2024)
The development of religious and moral values is the main foundation that must be instilled in children from an early age. To develop these values at RA Arafah Sipolu-polu, Hajj rituals are implemented. This research aims to determine the implementation of Hajj rituals, supporting and inhibiting factors, and their impact on the development of religious and moral values for group B children at RA Arafah Sipolu-polu. This research uses a descriptive qualitative approach, with data obtained through interviews, observation and documentation from school principals and teachers. The research results show that: first, the Hajj ritual activities are carried out through three stages, namely opening, core and closing, with planning, implementation and evaluation steps. Second, supporting factors for this activity include support from the school principal, teachers, parents, as well as the children's enthusiasm for learning. Inhibiting factors include a shortage of teachers, the very active nature of children, low concentration of children, children who do not follow the rules, and the school environment. Third, the positive impact of Hajj rituals is that children know the fifth pillar of Islam, understand the procedures for Hajj rituals from an early age, know their religion from an early age, get used to doing good things, and make it easier for teachers to teach. The negative impact is the emergence of a high sense of belonging, children's minimal knowledge about Hajj rituals, and people's mindset about school.